Development and fabrication of pineapple rolled tart machine - Pua, Ming Yee; Shamsudin, Rosnah; Hamzah, Azman; Endan, Johari (Academic Journals, 2011)
A pineapple rolled tart machine is required in the manufacturing of pineapple rolled tart. In this research, a machine that would reduce processing time and operating cost and that would be affordable for small-scale industries was designed. The machine was tested at different screw rotating speeds and dough formulations. The rolled tart throughput rates were significantly increased (p<0.05) with screw rotating speeds and butter percentages of dough. However, it was significantly decreased (p<0.01) with sugar and corn flour percentages. The hardness of baked tart and the hardness and stickiness of unbaked tarts were not significantly different between various screw rotating speeds and manual method. It was found that the rolled tart produced by this machine was acceptable in texture and mouth feel. The maximum and minimum rates for the standard dough formula were 4320 and 720 pieces h-1.